KARAKTERISTIK KEKUATAN SAMBUNGAN PENGELASAN FRICTION STEER SPOT WELDING PADA PADUAN ALUMINIUM A5052 BERDASARKAN KEKUATAN FATIGUE - Fritz Alexander (2023)
This research aims to analyze the material response of Aluminium 5052 to repeated cyclic loading and identify the factors influencing the fatigue strength of FSSW joints. Fatigue testing was concluded using flat plate specimens with FSSW joints in Aluminium 5052. The specimens were prepared according to established protocols, and cyclic loading was applied with varying stress amplitudes and frequencies. Measurement of stress, deformation, and dimensional changes of the specimens were performed during the testing. The fatigue testing results demonstrated that the FSSW joints in Aluminium 5052 exhibit reliable fatigue strength characteristic. The fatigue curves showed a reduction in strength with increasing cycle numbers, but the crack growth rate tended to stabilize after an initial transitional period. Material properties of Aluminium 5052, such as tensile strength and hardness, also play a role in determining the fatigue strength of the FSSW joints. The FSSW joints in Aluminium 5052 exhibit adequate fatigue strength characteristics. This research provides further understanding of the material response of Aluminium 5052 to cyclic loading. The findings contribute to the development of engineering applications utilizing FSSW joints in Aluminium 5052.